Wybrane instrumenty rachunkowości zarządczej w systemie zarządzania projektami na przykładzie Wyższej Szkoły Informatyki i Zarządzania w Rzeszowie - Kaszuba-Perz, Adriana; Pydo, Sabina (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Systems of project management are the answer to the need of planning, steering and inspection in these areas of activity of an institution which are focused on projects. The most important aim of these systems is to deliver useful information, which properly used will permit to manage human and material resources effectively. This article presents the idea of introduction of the project management system at a university. Here are shown the main elements of this system and some tools of management accountancy used in it. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 118-129